Robotic assisted radical prostatectomy: a different treatment for prostate cancer? - Alexandre Den Julio; Thomas Edward Ahlering; Fernando Korkes; Antonio Correa Lopes Neto; Marcos Tobias-Machado; Antonio Carlos Lima Pompeo; Eric Roger Wroclawski (Einstein (São Paulo))
ABSTRACT Considering the Health Care System in Brazil, a developing country, and public healthcare policies, robotic surgery is a reality to very few citizens. Therefore, robotic assisted radical prostatectomy is far removed from the daily practice of the vast majority of Brazilian urologists. Scientific evidence of the superiority of robotic assisted radical prostatectomy does not presently justify public investments for widespread development of robotic centers. Maybe over time and with reductions in costs, robotic technology will become a more established practice, as observed in other countries, and more feasible for the Brazilian urological community.